STUDY ON THE EFFICACY OF AMITRAZ AND DELTAMETHRIN AS ACARACIDES AGAINST Boophilus microplus (CAMESTRINI, 1887) IN THE DAIRY AREA OF GOIÂNIA - GOIÁS - Silva, Maria do Carmo Lima (2007)
The efficacy of amitraz and deltamethrin as acaricides against Boophilus microplus (Canestrini, 1887) was evaluated through an in vitro immersion test using engorged female ticks collected in the dairy area of the microrregion of Goiânia, State of Goiás. The effectiveness of the experimental compounds, on concentrations of 250 ppm, was determined by the effect as measured in percentages of inhibited reproduction (%INR) after treatments of the ticks with liquid formulations. The results were: amitraz showed the best efficacy with a percentage of inhibited reproduction (%ITR) of 97.11%; for deltamethrin such value was 70.86%, which was considered very low to be used as an acaricide. KEY-WORDS: Boophilus microplus; acaricides; amidines; pyrethroids; cattle.